The role of cognitive function in the relationship between age and health literacy: a cross-sectional analysis of older adults in Chicago, USA. Issue 4 (23rd April 2015) - Kobayashi, Lindsay C; Smith, Samuel G; O'Conor, Rachel; Curtis, Laura M; Park, Denise; von Wagner, Christian; Deary, Ian J; Wolf, Michael S
Abstract : Objectives: To investigate how 3 measures of health literacy correlate with age and the explanatory roles of fluid and crystallised cognitive abilities in these relationships among older adults. Design: Cross-sectional baseline analysis of the 'LitCog' cohort study. Setting: 1 academic internal medicine clinic and 5 federally qualified health centres in Chicago, USA. Participants: English-speaking adults (n=828) aged 55–74 years, recruited from August 2008 through October 2011. Outcome measures: Health literacy was measured by the Test of Functional Health Literacy in Adults (TOFHLA) and the Newest Vital Sign (NVS), both of which assess reading comprehension and numeracy in health contexts, and by the Rapid Estimate of Adult Literacy in Medicine (REALM), which assesses medical vocabulary. Fluid cognitive ability was assessed through the cognitive domains of processing speed, inductive reasoning, and working, prospective and long-term memories, and crystallised cognitive ability through the verbal ability domain. Results: TOFHLA and NVS scores were lower at ages 70–74 years compared with all other age groups (p<0.05 for both tests). The inverse association between age and TOFHLA score was attenuated from β=−0.39 (95% CI −0.55 to −0.22) to β=−0.06 (95% CI −0.20 to 0.08) for ages 70–74 vs 55–59 years when fluid cognitive ability was added to the model (85% attenuation). Similar results were seen with NVS scores (68% attenuation). REALM scores did not differ by age group (p=0.971). Crystallised cognitive ability was stable across age groups, and did not influence the relationships between age and TOFHLA or NVS performance. Conclusions: Health literacy skills show differential patterns of age-related change, which may be explained by cognitive ageing. Researchers should select health literacy tests appropriate for their purposes when assessing the health literacy of older adults. Clinicians should be aware of this issue to ensure that health self-management tasks for older patients have appropriate cognitive and literacy demands.